Energy‐efficient physical layer packet authenticator for machine‐to‐machine networks1. Issue 4 (7th May 2013) - Bartoli, A.; Hernández‐Serrano, J.; León, O.; Kountouris, A.; Barthel, D.; Antón‐Haro, Carles; Lestable, Thierry; Lin, Yonghua; Nikaein, Navid; Watteyne, Thomas; Alonso‐Zarate, Jesus
ABSTRACT Machine‐to‐machine networks are spreading over every sector of our society due to their self‐organisation capabilities. In these networks, thousands of devices are left unattended for years of operation without the possibility of human intervention. In this sense, every step forward into avoiding early exhaustion of the network nodes is of paramount importance. We have introduced a novel authentication scheme that is able to discard non‐intended and/or non‐legitimate packets just after the reception of the physical preamble. This proposal was shown to yield enormous energy saving with regard to both node exhaustion attacks and normal network operation. In this paper, we extend that work with a novel synchronisation protocol that addresses previous desynchronisation issues. Besides, we analyse and propose the more appropriate deployment parameters that maximise the overall energy savings. We also detail the necessary key generation and key updating processes required to manage the in use keying material. Moreover, we show how to fit the proposed mechanism into the IEEE 802.15.4e amendment to the IEEE 802.15.4‐2006 standard, as many companies have decide to go for this technology for the development of machine‐to‐machine networks.Copyright © 2013 John Wiley & Sons, Ltd.